Improving the Timely Detection of Bladder and Kidney Cancer in Primary Care - Zhou, Yin (Adv Ther, 2019)
Bladder and kidney cancer are the 10th and 7th most common cancers in the United Kingdom (UK). They present with symptoms that are typically investigated via the same diagnostic pathway. However, diagnosing these cancers can be challenging, especially for kidney cancer, as many of the symptoms are non-specific and occur commonly in patients without cancer. Furthermore, the recognition and evaluation of these symptoms may differ because of the lack of supporting high-quality evidence to inform management, a problem also reflected in currently ambiguous guidelines. The majority of these two cancers are diagnosed following a referral from a general practitioner. In this article, we summarise current UK and United States (US) guidelines for investigating common symptoms of bladder and kidney cancer—visible haematuria, non-visible haematuria and urinary tract infections. Our article aims to support clinicians in recognising and investigating patients with symptoms of possible bladder and kidney cancer in a timely fashion. We discuss challenges during the diagnostic process and possible future interventions for improvement.